- #1

Monoxdifly

MHB

- 284

- 0

\(\displaystyle log_2(x+2)+log_{(x-2)}4=3\)

I said I had no idea because one is x + 2 and the other one is x - 2. If both are x + 2 or x - 2, I can do it. He said that if that's the case, even at his level he could solve it. This is what I've done so far regarding the question.

\(\displaystyle log_2(x+2)+log_{(x-2)}4=3\)

\(\displaystyle \frac{log(x+2)}{log2}+\frac{log4}{log(x-2)}=3\)

\(\displaystyle \frac{log(x+2)log(x-2)+log4log2}{log2log(x-2)}=3\)

\(\displaystyle log(x+2)log(x-2)+2log^22=3log2log(x-2)\)

\(\displaystyle log(x+2)log(x-2)-3log2log(x-2)=-2log^22\)

\(\displaystyle log(x-2)(log(x+2)-3log2)=-2log^22\)

What should I do from here? Or did I make some mistakes?